2020
DOI: 10.3762/bjnano.11.24
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of data-cube pump–probe KPFM on organic solar cells

Abstract: An implementation of pump–probe Kelvin probe force microscopy (pp-KPFM) is reported that enables recording the time-resolved surface potential in single-point mode or over a 2D grid. The spectroscopic data are acquired in open z-loop configuration, which simplifies the pp-KPFM operation. The validity of the implementation is probed by measurements using electrical pumping. The dynamical photoresponse of a bulk heterojunction solar cell based on PTB7 and PC71BM is subsequently investigated by recording point-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 42 publications
(56 reference statements)
0
28
1
Order By: Relevance
“…The so-called pump–probe-based approaches have been used in optical spectroscopy for decades and recently have been applied to electric SPM modes in order to resolve the local decay of the surface photovoltage in organic donor–acceptor blends, V cpd changes in an organic transistor structure with microsecond temporal resolution, and picosecond relaxations of photovoltage in low-temperature grown GaAs. 24 , 27 , 28 Limitations and possible artifacts of this approach have also been investigated by a number of groups. 27 , 29 Murawski et al reported on a dual-closed loop system that removes crosstalk artifacts in the topography channel originating from an incorrect voltage applied by the KPFM feedback loop.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The so-called pump–probe-based approaches have been used in optical spectroscopy for decades and recently have been applied to electric SPM modes in order to resolve the local decay of the surface photovoltage in organic donor–acceptor blends, V cpd changes in an organic transistor structure with microsecond temporal resolution, and picosecond relaxations of photovoltage in low-temperature grown GaAs. 24 , 27 , 28 Limitations and possible artifacts of this approach have also been investigated by a number of groups. 27 , 29 Murawski et al reported on a dual-closed loop system that removes crosstalk artifacts in the topography channel originating from an incorrect voltage applied by the KPFM feedback loop.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches enable non-invasive imaging down to picosecond temporal resolution 21,22 . Improvement of the time resolution has been achieved by various means, such as recording the cantilever deflection read-out signal with ultra-high sampling rate as well as by overcoming the averaging limitation by applying high frequency pulses in excitation and detection [23][24][25][26] . The latter so-called pump-probe based approaches have been used in optical spectroscopy for decades and recently have been applied to SPM in order to resolve the local decay of the surface photovoltage in organic donor-acceptor blends, contact potential difference (CPD) changes in an organic transistor structure with microsecond temporal resolution, and picosecond relaxations of photovoltage in low temperature grown GaAs 27,28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the observations made from KPFM measurements on D/A bulk heterojunctions, where local variations of SPV have been attributed to local phase composition and/or morphology changes. [ 46 ] The latter observation could come from the fact that the shape and spatial extent of the molecular orbitals probed at +0.5 V (empty states) are not identical to those measured at −0.5 V (occupied states). Nevertheless, we observe no obvious correlation between the profiles ΔhSTM± and ΔIω± (from Figure 6b), which tends to prove that the dissymmetry of the photocurrents measured at the D/A junction level does not come from a variation between the exponential decays of the molecular states′ wave functions probed in the tunnel junction at + V t and − V t , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This understanding can be achieved by performing macroscopic optical measurements, e.g., current‐voltage [ 5 ] and photoluminance, [ 6 ] in conjunction with scanning probe microscopy (SPM) with high spatial resolution, [ 7 ] such as conductive atomic force microscopy (c‐AFM), [ 8 ] which maps electronic transport capability, [ 9 ] ion migration, [ 10 ] surface hysteresis, [ 11 ] ferroelectric polarization, [ 12 ] and face orientation of PSCs. [ 11,13 ] In addition to c‐AFM, Kelvin probe force microscopy (KPFM) has been implemented to evaluate the device performance [ 14 ] and to gain an improved understanding of the local charge carrier movement mechanism, which includes charge carrier generation, [ 15 ] accumulation, [ 16 ] recombination, [ 17 ] transport, [ 18 ] relaxation, [ 19 ] and extraction at the electrode. [ 7a,20 ]…”
Section: Introductionmentioning
confidence: 99%